Dependable software engineering : theories, tools, and applications : third International Symposium, SETTA 2017, Changsha, China, October 23-25, 2017, Proceedings /: theories, tools, and applications : third International Symposium, SETTA 2017, Changsha, China, October 23-25, 2017, Proceedings. (2017) - Unknown
No abstract available